Teachers’ Capacity Building Through Professional Development Training Program: A Perceived Perspective of New Appointed Faculty of Ghazi University (Journal of Asian Development Studies, 2024)
This research on teachers' capacity building through professional development training programs is crucial as it addresses the evolving needs of newly appointed faculty at Ghazi University. In a rapidly changing educational landscape, professional development is key to enhancing teaching effectiveness, fostering pedagogical innovation, and improving student outcomes. The leadership of Ghazi University decided to organize the training session for newly appointed faculty to update their professionalism for the quality work at work place. This responsibility was given to the department of education, Ghazi University to conduct the capacity building session. Insightful support was ensured by the university bodies i.e. director ORIC, director QEC, director FAD, director academic, director IT, controller examinations and registrar office of the university. Population was confined to newly appointed faculty at Ghazi University in 2021 that was 133 in total. The census sampling technique was used to collect the data as the whole population was approached. Self-developed questionnaire at five point Likert type scale was used to gather the information. Cronbach alpha value of the tool was 0.948. Only 100 respondents responded. Analysis was done by applying mean score, standard deviation, Pearson correlation and multiple regression analysis. There was positive and significant correlation of teachers’ capacity building through professional development training program at university level. It was recommended that such training program must be conducted at university level for effective quality work.